New insights into the sources of atmospheric lead reaching the Arctic by isotopic analysis of PM10 atmospheric particles and resuspended soils - Grotti, Marco; Ardini, Francisco; Vecchio, Maria Alessia; Mataloni, Matilde; Bertinetti, Stefano; Bruschi, Federica; Moroni, Beatrice; Cappelletti, David; Hobin, Kasper; Vanhaecke, Frank (Atmospheric Environment, 2024)
Lead concentration, crustal enrichment factor, and isotope ratios (including those with the less abundant 204Pb) have been measured in PM10 samples collected at Ny-& Aring;lesund (Svalbard Islands) from October 2018 to November 2020, including, for the first time, the autumn and winter seasons. In addition, resuspended soil samples from Svalbard Islands, Iceland, and Alaska were prepared and analysed to provide reference values for local and short-range potential source areas, and back-trajectory analysis was applied to corroborate the findings based on the Pb isotopic signatures. Results showed that the atmospheric Pb concentration reached its maximum in January, progressively decreased until August, remained low until November, and increased again in December. The Pb isotopic composition also showed a clear temporal variation, indicating a shift in the Pb sources with the changing seasons, in agreement with the back-trajectory analysis results. Lead in PM10 samples collected from November to May was entirely (>99%) anthropogenic, and it likely derived from the mining activities in East Kazakhstan and the Altai region, specifically at Leninogorsk (now Ridder). In contrast, the Pb isotopic composition of particulate samples collected from June to October reflected mixed anthropogenic contributions from the North-East USA and Canada, with a significant contribution from natural sources.